Surface Functionalization of Natural Rubber by UV‐Induced Thiol‐ene Chemistry. Issue 1 (July 2016) - Manhart, Jakob; Kramer, Rebecca; Schaller, Raimund; Holzner, Armin; Kern, Wolfgang; Schlögl, Sandra
Summary: Natural rubber (NR) surfaces with tailored physicochemical properties and spatially controlled surface topology were prepared by exploiting radical‐mediated thiol‐ene chemistry. Selected functional thiols were immobilized onto NR surfaces by the photo‐induced addition reaction across the unsaturated CC double bonds of the cis ‐1, 4‐isoprene units. The modified elastomer surfaces are characterized by means of ATR FTIR spectroscopy to follow changes in the chemical surface composition, and by contact angle measurements to study changes in surface polarities. The results evidence the versatility of this photochemical functionalization route since different surface characteristics and surface reactivities were obtained, depending on the chemical nature of the attached thiol. In addition, the influence of the surface functionalization on bulk properties and surface morphology was determined by tensile tests and microscopic techniques, respectively. Results show that both tensile properties and surface morphology are not affected by the photochemical functionalization process. The immobilized thiols were further used as reactive anchor groups for a subsequent immobilization of inorganic silica particles, resulting in a well‐defined change in surface roughness and topology. Spatial control of surface properties was accomplished by photolithographic techniques that enabled a patterned immobilization of inorganic particles onto NR surfaces. Microscopic techniques revealed the selective coupling of the inorganic particles in the illuminated surface areas that were defined by high resolution and clear edges.